PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2015-2017 - Sari, Pande Made Yani Indah; Riasning, Ni Putu; Rini, Gst Ayu Intan Saputra (Program Studi Akuntansi Fakultas Ekonomi Universitas Mahasaraswati Denpasar, 2019)
The companyâ€™s failure is not because of competition, but because of corporate governance. CSR is considered as a burden for companies because companies have to pay extra for the imÂplementation of CSR which has an impact on dividend distribution. The purpose of this study is to determine the effect of GCG which is proxied by managerial ownership, institutional ownerÂship, independent board of commissioners, board of commissioners, and audit committee and CSR on ROA in manufacturing companies listed on the Indonesia Stock Exchange in the period 2015-2017. The data collection method used is documentation. The analysis technique used is multiple regression analysis. The results of this study stated that GCG and CSR have a positive effect on ROA which means that an increase in GCG and CSR activities can increase ROA.